ANALISIS PERBEDAAN PRODUKSI SUSU SAPI PERAH YANG DIBERI SUBSTITUSI PAKAN OKRA DAN KEDELAI EDAMAME DI BEST COW FARM JEMBER - Nunur Nuraeni; Arifin Arifin (JURNAL SAINS PETERNAKAN NUSANTARA, 2022)
The purpose of this study was to calculate the cost of feed and to find out whether there was a difference in milk production between dairy cows fed substituted with sort okra and edamame soybean. The research target is the Best Cow Farm dairy farm, Ajung District, Jember Regency. The method used in this study is a survey by collecting data on milk production and feed costs given to cows during lactation during 12 days of observation on 10 dairy cows at Best Cow Farm, Ajung, Jember. The results showed that the average cost of feed for dairy cows that were substituted for edamame soybeans was Rp. 19.250,- and those given forage okra were Rp. 19.125,- per head per day. The average milk production of dairy cows substituted for edamame soybeans is 4.76 liters and those given okra forage substitution is 7.03 liters per head per day. Based on the results of the t-test analysis, it showed that there was a difference between milk production that was substituted for edamame soybean forage and that was given okra forage substitution. Keywords : Dairy Production, Okra, Edamame Soybean, Jember